Case report: Musculoskeletal metastastic inflammatory myofibroblastic tumor (IMT) treated by sequential ALK-TKI with longterm response - Cochin, Thomas; Noal, Sabine; Stefan, Dinu; Bodet, Damien; Rouger, Jérémie; Dorbeau, Marine; Neviere, Zoé (Frontiers in Oncology, 2025)
Inflammatory myofibroblastic tumors (IMTs) are known to be associated with rearrangements of the anaplastic lymphoma kinase (ALK) gene. The treatment of this type of tumor includes systemic therapies such as chemotherapies or anti-inflammatories; in recent years, targeted anti-ALK therapies have emerged and became the standard of care in ALK rearranged patients. We aimed to present a rare case of musculoskeletal IMT with ALK rearrangement, characterized by metastatic evolution and enhanced responses to sequential treatment with all ALK-TKI. We have outlined a potential treatment pathway involving sequential ALK-TKI targeted therapies and successive local interventions to control the cancer.